2015
DOI: 10.1373/clinchem.2015.242339
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Testosterone and Fracture Risk in Men: A Comparison of RIA and LC-MS/MS

Abstract: BACKGROUND: Serum testosterone can be measured by LC-MS/MS and RIA. We investigated whether the testosterone-fracture relationship was affected by the method of measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…[ 22 , 23 ] Multiple studies have shown a significant decrease in bone density and an increased risk of brittle fractures in patients with low testosterone levels. [ 24 , 25 ] In addition, patients with prostate cancer who undergo androgen deprivation therapy or orchiectomy also experience decreased bone density and increased risk of fracture. [ 26 , 27 ] There is also a link between the testosterone and vitamin D pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 , 23 ] Multiple studies have shown a significant decrease in bone density and an increased risk of brittle fractures in patients with low testosterone levels. [ 24 , 25 ] In addition, patients with prostate cancer who undergo androgen deprivation therapy or orchiectomy also experience decreased bone density and increased risk of fracture. [ 26 , 27 ] There is also a link between the testosterone and vitamin D pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There was also evidence of a nonlinear association between androstenedione and percent-water; relative to women in the lowest quartile those in the second lowest had a 4% (0.96; 0.87-1.06) lower percent-water while those in the second and first highest quartiles had, respectively, a 2% (1.02; 0.92-1.13) and 1% (1.01; 0.92-1.12) higher percent-water ( Supplementary Table S3). Plasma testosterone levels at age 15.5 were weakly correlated with levels at age 21.5 (r ¼ 0.45; P < 0.001) despite the different measurement methodologies used (30). Neither adolescent nor young adult testosterone levels were found to be associated with MRI breast measures.…”
Section: Plasma Sex Hormones and Mri Breast Measuresmentioning
confidence: 93%
“… 11 Other studies have found a concordance between LC/MS and RIA in the measurement of total testosterone. 13 In a study on 56 men (aged 26–77 years) comparing RIA and EqD, a robust correlation ( r = 0.966) in results was observed, 14 but as this study was performed with samples from normal, healthy men, the measurements were not at the lower end of the concentration spectrum where assay differences, if they exist, may be expected to occur.…”
Section: Resultsmentioning
confidence: 82%